Analisis Kandungan Cemaran Bakteri Coliform Pada Air Rendaman Tahu di Pabrik Tahu Wilayah Kalideres Jakarta Barat - Adelia Febriyossa; Melania Immaculata Koten (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Tofu is a food source containing high vegetable protein. Tofu is in great demand by most of the Indonesian people because it contains high nutrition and the price is relatively cheap and affordable. To produce tofu requires good hygiene and sanitation, such as providing clean raw materials and water sources that are free from contamination. To determine whether the water source has been contaminated with microbes or not, the Coliform bacteria indicator in the water sample is used. In testing Coliform bacterial contamination in water or raw materials, the Most Probable Number (MPN) method is used to calculate the amount or level of microbial contamination in determining the quality or quality of water and raw materials by referring to the MPN table. This study aims to determine the level of Coliform bacteria contamination in tofu soaking water in a tofu factory in the Kalideres area of ??West Jakarta. The design of this research is a descriptive laboratory type which was carried out in March-June 2020 at the Indonesian Social Solidarity STIKes Laboratory. Based on the results of the research on the presumptive test, it was found that 1 positive tube was contaminated with Coliform in the KR tofu factory and 3 positive tubes at the DN factory. The presumptive test was continued to confirmatory test and found 5 positive tubes polluted at the DD factory, 2 positive tubes at the KR factory and 3 positive tubes at the DN factory. The positive tube from the confirmation test was calculated for the contamination index value (MPN) and obtained 21000 mpn/ml for the DD factory, 4000 mpn/ml for the KR factory and 9000 mpn/ml for the DN factory. It can be concluded that there is Coliform bacterial contamination in all tofu soaking water samples in 3 tofu factories with the MPN index value having passed the contamination threshold.